Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Karyawan British Council Indonesia Di Jakarta - Trihantoro, Johan (Journal of Economics & Business UBS, 2019)
The purpose of this research is to know: (1) Influence of Training on Employee Performance at the British Council Indonesia, (2) Influence of Work Motivation to Employee Performance in the British Council Indonesia, and (3) Influence Training and Work Motivation to Employee Performance at the British Council Indonesia. The type of research used is survey. The population in this study is employees of the British Council Indonesia. The sampling technique used purposive sampling method with the number of samples counted 41 people. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis techniques used to answer the hypothesis is multiple regression. The results of this study show that: (1) Training variable has a positive effect on employee performance in British Council Indonesia. This is evidenced from the t-count of 3.454 with a significance value of <0.05, and the regression coefficient has a positive value of 0.327; (2) Work Motivation variable has a positive effect on employee performance in Britsih Council Indonesia. This can be proven from the tcount of 4.875, with a significance value of <0.05, and the regression coefficient has a positive value of 0.395; (3) Variables of Training, and Work Motivation simultaneously to employee performance in British Council Indonesia. This can be proven from the value of Fcount of 32.798 while Ftabel for n = 41 of 3.23, with significance <0.05.